Correlation between carotid intima-media thickness and serum TNF-alpha levels in female with rheumatoid arthritis of different ethnicities: A single-centre experience in Malaysia - Yi, Kek Xin; Wahab, Asrul A; Abas, Mohamad Norazrin Mohd; Wahid, Siti Amira Kamarul Abdul; Othman, Faridah Hanun; Said, Mohd. Shahrir Mohamed (UI Scholars Hub, 2019)
Background: Rheumatoid arthritis (RA) is a destructive chronic inflammatory disease with intra- and extra-articular manifestations. It is associated with accelerated formation of arteriosclerosis. The aim of this study was to ascertain the correlation between endothelial dysfunction using carotid intima–media thickness (cIMT) and tumor necrosis factor-alpha (TNF-α) levels among the three main ethnic groups in Malaysia: Malay, Chinese, and Indian. Methods: This cross-sectional study included 23 females with RA belonging to three different ethnic groups who were free from cardiovascular risk factors. Blood sample was taken from each patient to measure serum TNF-α level, C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR). Carotid ultrasonography was performed for cIMT analysis. The Disease Activity Score (DAS)-28 scoring system was used to assess disease activity. Results: Patients’ median age and disease duration were 47 and 5 years, respectively. No thickened cIMT was found in any of the patients. The duration of disease, TNF-α level, cIMT, DAS-28 CRP, and DAS-28 ESR showed no significant correlations in the different ethnic groups (p > 0.05). Conclusion: This study indicates that cIMT and serum TNF-α levels among females with RA in Malaysia may not be affected by ethnicity.